Integrating Tobacco Control and Obesity Prevention Initiatives at Retail Outlets - Ribisl, Kurt M. (Prev Chronic Dis, 2016)
Tobacco products are sold in approximately 375,000 US retail outlets, including convenience stores and pharmacies, which often sell energy-dense, low-nutrient foods and beverages. The Food and Drug Administration’s (FDA’s) increased authority over tobacco product sales and marketing, combined with declining smoking rates, provides an opportunity to transition tobacco retailers toward healthier retail environments. Unfortunately, research into improving consumer retail environments is often conducted in isolation by researchers working in tobacco control, nutrition, and physical activity. Interdisciplinary efforts are needed to transform tobacco retailers from stores that are dependent on a declining product category, to the sale and promotion of healthful foods and creating environments conducive to active living. The objective of this article is to describe the potential for interdisciplinary efforts to transition retailers away from selling and promoting tobacco products and toward creating retail environments that promote healthful eating and active living.